External Debt as a Stimulator of Economic Growth in Selected International Economies for the Period (2003-2022) - Ihab Abbas Al-Faisal; Basheer Hadi Auda Al-taai (مجلة الغري للعلوم الاقتصادية والادارية, 2025)
This study aims to analyze and measure the causal relationship between external debt and economic growth in three major industrialized countries: the United States, Japan, and China, over the period from 2003 to 2022. The core issue addressed by the study revolves around whether external debt can lead to positive outcomes that enhance economic growth, particularly given the variations in economic policies and the differing uses of external debt across the studied nations. The research methodology employed an econometric approach, utilizing (panel data) and causality tests. The findings revealed that external debt had a positive impact on economic growth in the three selected countries, effectively contributing to the enhancement of economic growth rates. Furthermore, differences in the magnitude of this impact were identified among the countries, with China ranking first in terms of the strength of the positive influence of external debt on economic growth, followed by Japan, and then the United States.